2023
DOI: 10.54112/bcsrj.v2023i1.438
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Surgery in Pakistan: A Swot Analysis

MUF MUJAHID,
Z BAIG

Abstract: The Sindh Government Qatar Hospital in Karachi installed Pakistan's first DaVinci S (DVS) system in 2011. Later, in 2013, Civil Hospital Karachi adopted more advanced DaVinci Si (DVSi) robotic equipment. Recently, in April 2023, the Pakistan Kidney and Liver Institute (PKLI) performed Radical Nephrectomy Robot-assisted Surgery. Essential search terms were finalized for a systematic review, and selection criteria were defined. The finalized keywords were entered into Pub-Med, Pakmedinet, and ERIC databases, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The strengths, weaknesses, opportunities, and threats (SWOT analysis) of robot-assisted surgery in Pakistan were published by Mujahid et al 15 Among the strengths identified are the huge number of patients in Pakistan, shorter hospital stays, and the incorporation of robotics into the surgeon's arsenal which will provide increased precision and comfort for future robotic surgeons while the main weaknesses identified were the Robotic systems' high initial and on-going costs along with absence of suitable training facilities and low research productivity in Pakistan. Furthermore, medical tourism, standardization, and multi-disciplinary technology all create opportunities for advancement.…”
Section: S-152mentioning
confidence: 99%
“…The strengths, weaknesses, opportunities, and threats (SWOT analysis) of robot-assisted surgery in Pakistan were published by Mujahid et al 15 Among the strengths identified are the huge number of patients in Pakistan, shorter hospital stays, and the incorporation of robotics into the surgeon's arsenal which will provide increased precision and comfort for future robotic surgeons while the main weaknesses identified were the Robotic systems' high initial and on-going costs along with absence of suitable training facilities and low research productivity in Pakistan. Furthermore, medical tourism, standardization, and multi-disciplinary technology all create opportunities for advancement.…”
Section: S-152mentioning
confidence: 99%